DEMONSTRASI PERAWATAN PAYUDARA PADA IBU MENYUSUI DI DESA ANUNGGANG JAE KECAMATAN PADANGSIDIMPUAN TENGGARA KOTA PADANGSIDIMPUAN TAHUN 2021 - Wiwi Wardani Tanjung; Elvi Suryani; Eva Yusnita Nasution (JURNAL PENGABDIAN MANDIRI, 2022)
Breast care in nursing mothers aims so that the breasts are always clean and easy to suck by the baby. Breast care can also help facilitate breast milk expenditure. With the treatment of the breast in the mother is expected nipples in a clean state, open alveoli, protruding nipples, flexing and strengthening the nipples released will meet the needs of the baby, as well as problems that can hamper the process of breastfeeding can be avoided. This community service activity aims to increase the knowledge of breastfeeding mothers on how to do breast care in Manunggang Jae Village, Padangsidimpuan District southeast of Padangsidimpuan City in 2021 so that mothers can do breast care themselves to facilitate breast milk expenditure. The method used in the implementation of this activity is a demonstration conducted directly to breastfeeding mothers. This activity as a means to increase the knowledge of breastfeeding mothers was previously given an explanation of how to follow the activity, then given material about breast care and then demonstrated breast care using phantom breasts. The results of this activity obtained an increase in the knowledge of breastfeeding mothers about breast care. You can do breast care on your own. It is expected that breastfeeding mothers can apply breast care at home every day to facilitate breast milk expenditure